Power and interests in conflicts over the use of irrigation channels in an informal settlement : a Peruvian perspective - Waselikowski, Lisa (SLU/Dept. of Urban and Rural Development, 2013)
Rapid and informal urbanisation is a phenomenon which is changing agricultural and natural landscapes into urban areas in an unplanned manner all over the world, especially in the global south. This has many consequences one of which is tension and conflict between traditional land users and urban settlers, leading to struggles over scarce resources.